Comparison of AI-enhanced educational games for students with disabilities - Taneska, Marija; Madevska Bogdanova, Ana (Scientific Technical Union of Mechanical Engineering" Industry 4.0", 2023)
In recent years, artificial intelligence (AI)-enhanced educational games have become powerful tools for people with disabilities. These games use AI algorithms to customize and personalize the learning experience to meet learners' unique needs and abilities. This comparative analysis aims to evaluate and compare different AI-powered educational games specifically developed for people with disabilities. This article attempts to provide insights so that developers, educators, and people with disabilities can use AI to select appropriate educational games. Highlights how AI-powered educational games can improve accessibility, engagement, and learning outcomes for people with disabilities.
Keywords: AI, educational games